Educator Profile from a Qur'anic and Hadith Perspective - Ahmad Yusam Thobroni; Dinda Kenanga Larasati; Afrida Nur Afni; Achmad Syaifudin Nur Khisam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The existence of educators and students is very important in the world of education. The role of educators is crucial because they are role models and guides for students. Educators who dedicate themselves must meet the requirements and carry out their duties well. For this reason, teachers need to understand the profile of educators from the perspective of the Qur'an and Hadith which includes murabbi, mu'allim, mu'addib, mudarris, and murshid. This research aims to understand the profile of educators according to the Al-Qur'an and Hadith. This research uses qualitative methods by collecting relevant literature sources. The research results state that educators have a heavy responsibility whose task is not only to transfer knowledge but also to form good character. Because of this, educators are required to treat students like their own children so that in the implementation process educators do not discriminate between students and can behave fairly.